Social Empowerment by Youth Organizations in the Development of Ijarah-Based MSMEs in Pamekasan Madura - Siran Wahyudi; Dwi Astutiek (Jurnal Ilmu Administrasi Negara, 2026)
This study aims to analyze the effect of E-Digital-based services on community satisfaction at the Public Service Mall (Mall Pelayanan Publik) in Sidoarjo. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to users of digital-based population administration services at the Public Service Mall Sidoarjo. The sampling technique used purposive sampling with a total of 100–150 respondents. Data analysis was conducted using descriptive analysis and simple linear regression. The results show that E-Digital-based services are categorized as good with an average score of 4.13, while community satisfaction is categorized as high with an average score of 4.21. The regression analysis indicates that E-Digital-based services have a positive and significant effect on community satisfaction. This implies that better digital service quality leads to higher levels of community satisfaction.However, several challenges remain, particularly related to system quality and digital literacy among the community. Therefore, improvements in technological infrastructure, human resource capacity, and public education on digital service utilization are necessary. This study is expected to contribute to the development of more effective, efficient, and responsive digital public services.